SYSTEM ACCEPTANCE OF STUDENT LEARNING IN MENTORING COURSE COMPUTER INSTITUTE GLOBAL EDUCATION CENTER (GEC) APPLICATIONS USING VISUAL BASIC 6.0 - Cincin Utami; Maria Sri Wulandari (Jurnal Sistem Informasi, 2010)
Admission tutoring students in this course more institutions ease of recording, toimprove accuracy and reduce the small error possible in the activities of theadmissions process. Save time in obtain information about the collection of studentdata reception classes primarily smooth running of teaching and learning. Providinginformation such as monthly reports about the amount of increase or not the numberof students to the leadership. And the analysis, it appeared that the New RegistrationSystem at MENTORING COURSE LEARNING IN INSTITUTIONS GlobalComputer Education Center (GEC), there is still less efficient the work of theirrespective existing functions. Therefore, there should be a better system and provideeasiness for students and the courses that underway, the author tries to make aninformation system the goal to be able to optimize the running system. And withauthors propose a system that is expected to provide convenience - convenience forstudents and the courses.